Probing metallo-β-lactamases with molecular fragments identified by consensus docking. Issue 22 (15th November 2015) - Klingler, Franca-Maria; Moser, Daniel; Büttner, Dominik; Wichelhaus, Thomas A.; Löhr, Frank; Dötsch, Volker; Proschak, Ewgenij
Graphical abstract: Abstract: Bacterial resistance mediated by metallo-β-lactamases (MBLs) is a major problem for the treatment of infections. An MBL inhibitor could restore the potency of β-lactam antibiotics. Fragment-based design might deliver valuable starting points for the discovery of novel MBL inhibitors. In this study, we chose an in silico approach to search for fragments able to bind and inhibit NDM-1, VIM-1, and IMP-7. We used consensus docking to identify low molecular weight compounds from a commercially available library. Most promising compounds were evaluated in a sensitive fluorescence-based activity assay and by the orthogonal biophysical technique saturation transfer difference (STD)-NMR. 1 H– 15 N chemical shift perturbation NMR was used to confirm the reversible binding and measure the dissociation constant of the most promising compound qualifying it as a high-quality starting point for further optimization.